Quality of Tax System Services at Bapenda of Pekanbaru City - Naulian, Lia; Hasanah, Nur; Novita, Wilda; Waty, Elly Niel (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to examine the quality of tax system services implemented in the Regional Revenue Agency (Bapenda) of Pekanbaru City. This study focuses on the importance of efficient and effective tax system service quality in increasing taxpayer satisfaction, as well as the challenges faced in implementing the tax system. The method applied in this research is a descriptive qualitative approach. Data was obtained through interviews, observation and documentation. The theory used in this study is the SERVQUAL model, which measures service quality based on five dimensions: physical evidence, reliability, responsiveness, assurance, and empathy. This research shows that overall, the Pekanbaru City Bapenda has succeeded in implementing good service quality indicators in increasing Taxpayer comfort and satisfaction. This research also states that the main challenge faced by the Pekanbaru City Bapenda in improving service quality is managing the manual tax system which has an impact on lower service efficiency, processing processes that take up to two weeks or more, long queues, and the potential for errors. man. Therefore, it is important for Bapenda to continue to evaluate and improve, especially in terms of the queuing system and the use of digital technology.